Education on Hygiene and Sanitation Standards for Ternate City MSMEs During a Pandemic at Sulamadaha Tourism Beach: Edukasi Standar Hygiene dan Sanitasi UMKM Kota Ternate Pada Masa Pandemi di Pantai Wisata Sulamadaha - Abd. Hakim Husen (Yayasan Ahmar Cendekia Indonesia, 2022)
In almost all parts of Indonesia, the Covid-19 pandemic situation has even had an impact on the temporary closure or delay of health and public services. The Covid-19 pandemic has also had a major impact on the economy throughout Indonesia, including in Ternate City, North Maluku Province. Problems found two main problems faced by PKM Partners, namely: Lack of Hygiene and Sanitation Standards in MSMEs that have not been optimal. Taking into account the above matters, the PKM Team agreed that it would overcome the problems with the scheduled program in PKM activities regarding the Hygiene and Sanitation Standards Training for Ternate City MSMEs during the Pandemic. The method used in this PKM activity is a participatory method. participation, participation or involvement related to the outward circumstances. Understanding the principle of participation is that the community plays an active role in the process or flow of the program stages and their supervision, starting from the socialization, planning, implementation, and preservation stages of activities by contributing energy, thoughts, or in the form of material. From the analysis of the situation and problems faced by Partners (MSMEs), it can be stated that the selection of health and business aspects is set to resolve and find solutions to Partner problems for activities Abstrak Hampir di seluruh wilayah Indonesia situasi pandemi Covid-19 bahkan berdampak pada penutupan sementara atau penundaan layanan kesehatan dan publik. Pandemi Covid-19 juga memberi dampak besar bagi perekonomian di seluruh Indonesia termasuk di Kota Ternate Provinsi Maluku Utara. Permasalahan ditemukan dua masalah utama yang dihadapi Mitra PKM, Yaitu: Minimnya Standar Hygiene dan Sanitasi pada UMKM yang belum optimal. Dengan mempertimbangkan perihal diatas, maka Tim PKM bersepakat bahwa akan mengatasi permasalahan dengan program yang terjadwal pada kegiatan PKM tentang Pelatihan Standar Hygiene dan Sanitasi UMKM Kota Ternate Dimasa Pandemi. Metode yang digunakan dalam kegiatan PKM ini adalah metode partisipatif. keikutsertaan, peran serta atau keterlibatan yang berkitan dengan keadaaan lahiriahnya pengertian prinsip partisipasi adalah masyarakat berperan secara aktif dalam proses atau alur tahapan program dan pengawasannya, mulai dari tahap sosialisasi, perencanaan, pelaksanaan, dan pelestarian kegiatan dengan memberikan sumbangan tenaga, pikiran, atau dalam bentuk materil. Dari analisis situasi dan permasalahan yang dihadapi Mitra (UMKM), maka dapat dinyatakan pemilihan aspek kesehatan dan bisnis yang ditetapkan untuk menyelesaikan dan mencari solusi untuk permasalahan Mitra untuk kegiatan.